DEVELOPING PRIORITY LEVEL OF MANGROVE REPLANTING SITES USING ENVIRONMENT, CLIMATE AND SOCIO-ECONOMIC DATA PRODUCT - Nurlaila Syahid, Luri
Mangroves have many benefits both for humans and for the surrounding ecosystem. However, the mangrove area experienced a decline from 1980 to 2005. The loss of mangroves resulted in many losses both in the economic sector and the disruption of the surrounding ecosystem. To overcome the decreasing mangrove land, mangrove rehabilitation and restoration efforts are needed. Therefore, the purpose of this study is to analyze the suitability of mangrove land in Southeast Asia using environmental, climate and socio-economic parameters. The environmental parameters are elevation and slope, while the climate and socio-economic parameters in question are air temperature, precipitation, land use land cover (LULC), population, gross domestic product (GDP), and night light. Besides, this study also uses global climate model data (GCM) from CNRM-CM5.1 and the MIROC5 for 2050 and 2070. Both models have three Representative Concentration Pathways (RCP) scenarios, namely RCP 2.6, 4.5 and 8.5. The data used as parameters in this study from the two models are precipitation data and average air temperature. All environmental and climate parameters both actual and predicted 2050 and 2070 are given different weights. The weight determination method used in this study is the Multi-Criteria Decision Making (MCDM) method with the Analytic Hierarchy Process (AHP) technique. The results of the AHP technique show that the most important parameter in determining land suitability for mangrove planting is tidal inundation. The results of this study indicate that potential land suitable for mangrove planting in Southeast Asia is currently around 398,000 ha. Besides, the most potential country that has very suitable for mangrove planting is Indonesia, with a percentage of 67.34% of the total land area in the very suitable class category and the appropriate class. Followed by Vietnam (10.52%), Philippines (6.62%), Thailand (5.38%), Malaysia (4.18%), and Cambodia (3.29%). However, the countries that have the least land to plant mangroves are Myanmar (2.57%), Brunei (0.09%) and Singapore (0.02%). The results of the potential suitability of mangrove land in 2050 show that RCP 8.5 is the scenario which has the most amount of land in the class category very suitable in almost all Southeast Asian countries. In contrast to 2050, the potential suitability of mangrove land in 2070 shows that the majority of countries in Southeast Asia have the same number of areas in the same class category in all three RCPs.